ONA TILI DARSLARIDA RIVOYA MATN USTIDA IShLAShGA OID ALGORITMIK TOPShIRIQLAR - Baynazarova, J.J. (SCIENCE and SOCIETY, 2025)
This article explores the effectiveness of using algorithmic tasks when working with rivoyat (didactic folk tale) texts in native language lessons. It highlights how such tasks develop students' thinking skills, text analysis abilities, and capacity to make meaningful conclusions. The algorithmic approach supports step-by-step analysis of the text, identification of its compositional structure, interpretation of characters, and the revelation of its main idea.
Keywords: native language; algorithmic tasks; text analysis; learning activity; thinking